A mold for preparing imitation stone facing brick decorative layer, imitation stone facing brick and preparation method thereof
By adopting a mold with a double-layer silicone film sandwich structure, the preparation of imitation stone face tiles with multiple patterns under the same mold frame is achieved, which solves the mirror effect and high cost problems in the preparation process of imitation stone face tiles in the prior art, and realizes efficient and low-cost production of imitation stone face tiles.
Patent Information
- Application Number
- CN202411981600.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-04
AI Technical Summary
In the existing imitation stone surface brick preparation process, imitation stone surface bricks prepared by dry method cannot achieve the effect of mirror imitation stone, while imitation stone bricks prepared by wet method require cutting and polishing technology, with low output and high cost, and lack technical processes that take into account the advantages of both processes and avoid their shortcomings.
Using a mold including an outer mold, an inner mold, a first silicone film and a second silicone film, a double-layer silicone film sandwich structure is used to prepare imitation stone surface tiles of multiple patterns under the same mold frame, eliminating cutting, grinding, polishing and other processes.
The preparation of imitation stone surface tiles with multiple patterns under the same mold frame is realized, saving preparation costs, improving production efficiency, and forming a mechanical joint between the decorative shell and the filling layer through the sawtooth structure to enhance the bonding effect and avoid cracking problems.
Smart Images

Figure CN119748612A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to a mold for preparing imitation stone facing bricks, the imitation stone facing bricks and a preparation method thereof. Background Art
[0002] At present, the mainstream preparation processes of imitation stone tiles on the market are mainly dry method and wet method. Although the imitation stone tiles prepared by the dry method can meet the needs of most cases in the market, they cannot achieve the effect of mirror imitation stone. Although the imitation stone tiles prepared by the wet method can produce mirror imitation stone texture, they need cutting and polishing processes, with low output and high cost. At present, there is no technical process that can take into account the advantages of the two preparation processes and avoid their disadvantages. Summary of the invention
[0003] In view of this, the purpose of the present invention is to provide a mold for preparing imitation stone tiles and imitation stone tiles and a preparation method thereof. The mold provided by the present invention can realize the preparation of imitation stone tiles with various patterns under the same mold frame, while eliminating the process of cutting, grinding, polishing, etc., saving the preparation cost.
[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0005] The present invention provides a mold for preparing a stone-like surface tile decorative layer, comprising an outer mold, an inner mold, a first silicone film attached to the inner wall surface of the outer mold, and a second silicone film attached to the outer wall surface of the inner mold;
[0006] The outer mold and the inner mold both have groove structures, and the first silicone film and the second silicone film are opposite to each other and a space is formed between them;
[0007] The first silicone film is a smooth silicone film or a silicone film with imitation stone patterns engraved on the surface; the second silicone film is provided with a plurality of first strip saw teeth arranged horizontally and in parallel on the side relative to the first silicone film, and a plurality of second strip saw teeth arranged in parallel on the bottom surface, the cross-section of the first strip saw teeth is square, the second strip saw teeth are inverted pyramidal shapes, and the second strip saw teeth are parallel to the first strip saw teeth.
[0008] Preferably, the thickness of the first silicone film is 3-5 mm, and the Shore hardness is 25-28 HA; the thickness of the second silicone film is 15-20 mm, and the Shore hardness is 28-35 HA.
[0009] Preferably, the outer mold and the inner mold are made of steel; and the first silicone film is magnetic.
[0010] Preferably, the height of a single first strip-shaped sawtooth is 8-10 mm, and the width is 8-10 mm; the spacing between adjacent first strip-shaped sawtooths is 10-20 mm.
[0011] Preferably, the top surface width of a single second strip-shaped sawtooth is 8 to 12 mm, the bottom surface width is 4 to 6 mm, the height is 8 to 12 mm, and the spacing between adjacent second strip-shaped sawtooths is 20 to 25 mm.
[0012] Preferably, the connection between the second silicone film and each surface of the first silicone film is rounded.
[0013] The present invention provides a method for preparing a stone-like surface tile, comprising the following steps:
[0014] Pour the color paste into the main paste, inject the obtained paste into the space between the first silicone film and the second silicone film in the mold described in the above technical solution for molding, and obtain the stone decorative shell blank after demoulding;
[0015] Curing the stone decorative shell blank to obtain a stone decorative shell;
[0016] Filling the cavity of the stone decorative shell with recycled concrete or recycled mortar to obtain the imitation stone facing brick;
[0017] The main slurry includes the following components in parts by weight:
[0018] 220-300 parts of white cement, 15-30 parts of silica fume, 60-130 parts of mineral powder, 1-5 parts of redispersible latex powder, 1-5 parts of attapulgite, 180-250 parts of heavy calcium carbonate, 1-3 parts of short fiber, 30-90 parts of first regenerated sand, 60-150 parts of second regenerated sand, 90-180 parts of third regenerated sand, 200-300 parts of fourth regenerated sand, 120-200 parts of regenerated stone powder, 1-5 parts of defoamer, 3-8 parts of styrene-acrylic emulsion, 10-15 parts of water reducer, 180-210 parts of water;
[0019] The color paste includes the following components in parts by weight:
[0020] 220-300 parts of white cement, 15-30 parts of silica fume, 60-130 parts of mineral powder, 1-5 parts of redispersible latex powder, 1-5 parts of attapulgite, 180-250 parts of heavy calcium carbonate, 1-3 parts of short fiber, 30-90 parts of first regenerated sand, 60-150 parts of second regenerated sand, 90-180 parts of third regenerated sand, 200-300 parts of fourth regenerated sand, 120-200 parts of regenerated stone powder, 1-5 parts of defoamer, 3-8 parts of styrene-acrylic emulsion, 10-15 parts of water reducer, 20-35 parts of pigment, 180-210 parts of water;
[0021] The particle size of the first regenerated sand is 1.25-2.5 mm, the particle size of the second regenerated sand is 0.63-1.25 mm, the particle size of the third regenerated sand is 0.315-0.63 mm, and the particle size of the fourth regenerated sand is 0.15-0.315 mm.
[0022] Preferably, in the main paste and color paste, the white cement is ordinary Portland cement, and the strength grade of ordinary Portland cement is P.O42.5 or above; the specific surface area of silica fume is 20 to 28 m 2 / g, with an average particle size of 0.1-0.3μm; the mineral powder is S95 grade mineral powder; the short fiber is polypropylene fiber with a length of 8-10mm; the particle size of the regenerated stone powder is below 0.045mm.
[0023] Preferably, the main slurry also includes 1 to 3 parts of a wetting agent.
[0024] The present invention provides an imitation stone facing tile prepared by the preparation method described in the above technical solution, wherein the imitation stone facing tile comprises a stone decorative shell and a filling layer combined in the cavity of the stone decorative shell, wherein the filling layer is recycled concrete or recycled mortar, and the interface between the stone decorative shell and the filling layer forms a mechanical bite through a serrated structure.
[0025] The present invention provides a mold for preparing a decorative layer of imitation stone tiles, comprising an outer mold, an inner mold, a first silicone film attached to the inner wall surface of the outer mold, and a second silicone film attached to the outer wall surface of the inner mold; the outer mold and the inner mold are both groove structures, the first silicone film and the second silicone film are opposite to each other and a space is formed between them; the first silicone film is a smooth silicone film or a silicone film with imitation stone patterns engraved on the surface; the second silicone film is provided with a plurality of first strip-shaped saw teeth arranged horizontally in parallel on the side relative to the first silicone film, and a plurality of second strip-shaped saw teeth arranged in parallel on the bottom surface, the first strip-shaped saw teeth have a square cross-section, the second strip-shaped saw teeth are inverted pyramidal shapes, and the second strip-shaped saw teeth are parallel to the first strip-shaped saw teeth. Compared with the prior art, the present invention has the following beneficial effects:
[0026] The mold provided by the present invention is provided with a double-layer silicone membrane structure, the space between the double-layer silicone membrane is used to cast the slurry of the imitation stone face brick decorative layer, the outer surface silicone membrane (i.e., the first silicone membrane) shapes the texture of the decorative surface layer, including any manufacturable shapes such as smooth surface, relief, and imitation stone rough surface, and the inner surface silicone membrane layer (i.e., the second silicone membrane) constructs a cavity for filling recycled mortar or recycled concrete, and at the same time, a mechanical bite (mortise and tenon) structure is constructed on the inner wall of the cavity to create conditions for the bonding of the filling layer; and, by selecting the first silicone membrane with different artistic effects, the cutting and polishing processes can be omitted, and the silicone membrane is cheap in cost, and while meeting the requirements of acid and alkali resistance and tear resistance, various patterns including mirror surfaces can be quickly reproduced according to sample requirements, and one mold can be used for multiple purposes, thereby greatly improving production efficiency and effectively reducing production costs;
[0027] Furthermore, the present invention adopts a silicone film with magnetism, which can better fit the steel outer mold fixture than ordinary silicone film, reduce the deformation of the mold and the use of auxiliary equipment. On the other hand, after the decorative layer slurry is poured into the mold, the aggregate particles containing iron and nickel components (such as regenerated sand and regenerated stone powder) inside sink and adhere to the bottom and side walls of the mold under the guidance of magnetic force, which can improve the surface hardness and wear resistance of the decorative shell.
[0028] The present invention provides a method for preparing a stone-like surface tile, which has the following beneficial effects:
[0029] The decorative shell prepared by the double silicone film sandwich structure mold is a separately cast individual. In the early stage when its own strength is insufficient, it does not need to be in direct contact with the base interface. Therefore, the problem of mortar cracking due to the large difference in bonding effect at the interface between the filling layer and the decorative shell can be avoided. Furthermore, the corners of the joints on each side of the cavity are rounded to disperse the tensile stress.
[0030] The present invention avoids a large number of factors that cause cracking in the early stage of the strength development of the decorative shell due to the lack of external force intervention, and then finely matches the particle size of aggregate particles according to the standard grading curve by adding short fibers, polymer powder (i.e., redispersible latex powder), styrene-acrylic emulsion and aggregate particles, and further restrains the influence of self-hydration shrinkage by adding mineral admixtures (mineral powder, silica fume) in the cementitious material system to reduce the shrinkage rate of cement hydration reaction, thereby successfully inhibiting the early shrinkage cracking of the decorative layer shell until the shell strength can completely overcome its own shrinkage stress; after the maintenance is completed, the cavity is filled with newly mixed recycled mortar or recycled concrete, At this time, the serrated structure on the inner surface of the shell of the decorative layer can provide a strong mechanical bite force, which can effectively make up for or even completely provide a sufficient fitting effect without relying on the bonding of the interface between the new and old mortars. The reason is that the inner surface of the shell provides a large number of serrated structures, the embedding depth and width can meet the penetration of the mortar, and each serrated tooth is placed upside down to form a structure similar to a mortise and tenon joint. After the mortar enters and solidifies, it can effectively lock the inner surface of the decorative shell so that it cannot move in all directions, thereby achieving a firm and irreversible locking effect. Finally, the decorative shell and the internal filling layer form a complete whole, that is, the decorative layer can be prevented from cracking.
[0031] The decorative shell material adopts a combination of high-flow self-compacting slurry material and a mirror silicone film layer to ensure that there is no need for cutting and polishing processes, greatly improving production efficiency and effectively reducing production costs;
[0032] The volume provided by the internal cavity of the decorative shell layer can reach more than 88% of the volume of the entire imitation stone face tile (panel), and a large amount of space inside it can be filled with recycled concrete and recycled mortar prepared from construction waste, and can even be directly filled with some concrete fragments that have not been crushed and screened. Compared with the wet process and the dry process, it has a wider source of raw materials and can be replaced by a large number of cheap construction waste products, with significant cost advantages;
[0033] The structure of the double-layer silicone membrane can quickly and non-destructively replace the decorative surface shape while omitting the mold cleaning process. The reason is that silicone is an organic polymer material with strong acid and alkali resistance and does not chemically react with cement-based inorganic materials. Even if it is contaminated with cement slurry during pouring, it can be cleaned by gently vibrating after demoulding. Therefore, the membrane surface structure will not be damaged during its service life.
[0034] The preparation method provided by the present invention can effectively avoid shrinkage and cracking during the early preparation and maintenance of the cement-based imitation stone brick facing layer on the basis of consuming a large amount of construction waste, improve the yield, and prepare various types of imitation stone bricks at a low cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 is a cross-sectional view of a mold for preparing a stone-like surface tile decorative layer in the present invention, Figure 1(a) is the overall effect diagram, (b) is the partial enlarged diagram, Figure 1 In the figure, 1-outer mold, 2-inner mold, 3-first silicone film, 4-second silicone film, 5-inner and outer mold fixing clamps, 6-fixing screws, 7-inflating hole;
[0036] Figure 2 The left view, right view and top view of the mold used for preparing the imitation stone surface tile decorative layer in the present invention;
[0037] Figure 3 Schematic diagram of the fillet (i.e. chamfer) at the connection between the two surfaces of the second silicone film. Figure 3 (a) is the top view, (b) is the left view, and (c) is the front view. Figure 3 In the figure, 8-the rounded corners at the connection between the side walls of the second silicone membrane, 9-the rounded corners at the connection between the side walls of the second silicone membrane and the bottom surface, 10-the rounded corners at the connection between the side walls of the second silicone membrane and the bottom surface;
[0038] Figure 4 This is a schematic diagram of the structure of the silica gel containing iron powder after casting when preparing the silica gel film with magnetic properties in the present invention. Figure 4 (a) is the top view, (b) is the left view, (c) is the right view, and (d) is the main view. Figure 4 In the figure, 11-silicone film containing iron powder, 12-silicone master mold;
[0039] Figure 5 Schematic diagram of the serrations on the side of the second silicone film (side view, front view and top view);
[0040] Figure 6 Schematic diagram of the sawtooth on the bottom surface of the second silicone film (side view, front view and top view);
[0041] Figure 7 is a schematic diagram of the structure of the imitation stone facing brick in the present invention, Figure 7 In the figure, (a) is a cross-sectional view of the imitation stone facing brick, and (b) is a partial enlarged view of the cross-sectional view. Figure 7 In the middle, 13-decoration layer, 14-filling layer, 15-serrated structure;
[0042] Figure 8 This is an appearance effect diagram of the decorative layer of the imitation stone facing brick prepared in Example 1;
[0043] Fig. 9 This is a wrapping effect diagram of the decorative shell + filling layer of the imitation stone facing brick prepared in Example 1. DETAILED DESCRIPTION
[0044] The present invention provides a mold for preparing a stone-like surface tile decorative layer, comprising an outer mold, an inner mold, a first silicone film attached to the inner wall surface of the outer mold, and a second silicone film attached to the outer wall surface of the inner mold;
[0045] The outer mold and the inner mold both have groove structures, and the first silicone film and the second silicone film are opposite to each other and a space is formed between them;
[0046] The first silicone film is a smooth silicone film or a silicone film with imitation stone patterns engraved on the surface; the second silicone film is provided with a plurality of first strip saw teeth arranged horizontally and in parallel on the side relative to the first silicone film, and a plurality of second strip saw teeth arranged in parallel on the bottom surface, the cross-section of the first strip saw teeth is square, the second strip saw teeth are inverted pyramidal shapes, and the second strip saw teeth are parallel to the first strip saw teeth.
[0047] In the present invention, the mold for preparing the imitation stone tile decorative layer is as follows Figure 1 and Figure 2 As shown, Figure 1 In the figure, 1-outer mold, 2-inner mold, 3-first silicone film, 4-second silicone film, 5-inner and outer mold fixing clamp, 6-fixing screw, 7-inflating hole. The following is a detailed description.
[0048] The mold for preparing the imitation stone facing tile decorative layer provided by the present invention comprises an outer mold and an inner mold. In the present invention, the material of the outer mold and the inner mold is preferably steel. In the present invention, the inner mold is preferably a movable structure, such as setting the inner mold to be split, so as to facilitate subsequent demolding; the outer mold is preferably a fixed structure, and the center of the bottom plate of the outer mold is preferably reserved with an inflation hole for inflation and demolding. In the present invention, the inner diameter size of the outer mold corresponds to the size of mainstream products on the market, such as 300×300×60mm, 600×600×60mm, and the outer diameter of the inner mold is the inner diameter of the outer mold minus the thickness of the decorative layer, the first silicone film and the second silicone film.
[0049] The mold for preparing the imitation stone surface tile decorative layer provided by the present invention comprises a first silicone film attached to the inner wall surface of the outer mold and a second silicone film attached to the outer wall surface of the inner mold, the first silicone film and the second silicone film are opposite to each other and form a space therebetween.
[0050] In the present invention, the thickness of the first silicone film is preferably 3 to 5 mm, and the Shore hardness is preferably 25 to 28 HA. In the present invention, the first silicone film is a smooth silicone film or a silicone film with imitation stone patterns engraved on the surface. The smooth silicone film is a smooth and flat silicone film, which can be a mirror silicone film. The patterns in the silicone film with imitation stone patterns engraved on the surface can be set according to the actual needs of the facing brick decorative layer, such as being set to relief, imitation natural stone shape, etc. In the present invention, the thickness of the first silicone film layer is only 3 to 5 mm, the cost is low, and it meets the requirements of acid and alkali resistance and tear resistance. At the same time, it can quickly replicate various patterns and styles according to existing samples, and one mold can be used for multiple purposes.
[0051] In the present invention, the first silicone film is preferably magnetic. The magnetic silicone film is more closely attached to the steel outer mold fixture than the ordinary silicone film, reducing the deformation of the mold and the use of auxiliary equipment. On the other hand, after the decorative layer slurry is poured into the mold, the aggregate particles containing iron and nickel components inside sink and adhere to the bottom and side walls of the mold under the guidance of magnetic force, which can improve the surface hardness and wear resistance of the decorative shell.
[0052] In an embodiment of the present invention, the magnetic silicone film is preferably prepared from the following raw materials in parts by weight: 800-1000 parts of liquid silicone, 500-800 parts of pure iron particles, 5-10 parts of silane coupling agent, and 20-30 parts of silicone curing agent; the preparation method of the magnetic silicone film is preferably: pouring liquid silicone, pure iron particles, silane coupling agent and silicone curing agent into a planetary mixer for mixing; pouring the resulting mixture on the surface of a mold (i.e., a silicone master mold) (such as Figure 4 As shown, Figure 4 The dotted outline in the figure represents the silicone master mold), which is then sent to an oven for curing (or self-curing), and the mold is removed to obtain a silicone semi-finished product; the silicone semi-finished product is spread open and inserted into a brick mold with strong magnetic magnet blocks pasted inside. The magnet blocks magnetize the iron powder evenly dispersed in the silicone semi-finished product to obtain a magnetic silicone film.
[0053] In the present invention, the liquid silicone is preferably industrial translucent liquid silicone, the Shore hardness is preferably 25-28HA, and the dynamic viscosity is preferably 25,000±0.2 ten thousand Pa·s; the silicone curing agent can be selected to match the liquid silicone; in an embodiment of the present invention, the liquid silicone is the cultural stone mold silicone produced by Shenzhen Hongtu Silicone Technology Co., Ltd., and the silicone curing agent is a curing agent matching Shenzhen Hongtu Silicone Technology Co., Ltd. In the present invention, the particle size of the pure iron particles is preferably 0.15-0.315mm. The present invention has no special requirements for the silane coupling agent, and a silane coupling agent well known to those skilled in the art can be used. In the present invention, the rotation speed of the planetary mixer is preferably 100r / min, and the stirring time is preferably 2-3min. In the present invention, the curing temperature is preferably 65-80°C, and the time is preferably 3-4h. In the present invention, the magnet block is preferably a permanent ferrite magnet. In an embodiment of the present invention, the magnet block has an outer size of 20×10×5 mm, a brand name of Y32, and is manufactured by Dongguan Saishi Magnetics and Electrics Technology Co., Ltd.; the magnetization time is preferably 20 to 24 hours.
[0054] In the present invention, the distance between the first silicone film and the second silicone film is the thickness of the decorative layer after the shell layer is formed. The thickness is set according to the strength requirement. In an embodiment of the present invention, the distance between the first silicone film and the second silicone film is set to 8 to 25 mm.
[0055] In the present invention, the thickness (including serrations) of the second silicone film is preferably 15-20 mm, the Shore hardness is preferably 28-35 HA, and the Shore hardness of the second silicone film is preferably greater than that of the first silicone film. In the present invention, the first silicone film has a relatively small hardness, which can better fit the inner diameter of the outer mold, especially for the magnetic silicone film, which has a higher softness and fit; the second silicone film has a relatively high hardness, which is more beneficial to the shaping of the serration structure on its surface, and will not cause deformation of the serrations. At the same time, it is more beneficial to the shaping of the shape of the internal space, and will not deform under the extrusion of the slurry to cause imbalance of internal stress.
[0056] In the present invention, the side of the second silicone membrane relative to the first silicone membrane is provided with a plurality of first strip-shaped saw teeth arranged horizontally and in parallel, and the bottom surface is provided with a plurality of second strip-shaped saw teeth arranged in parallel, the cross section of the first strip-shaped saw teeth is square, the second strip-shaped saw teeth are inverted prisms (i.e., the cross section is an inverted trapezoid), and the second strip-shaped saw teeth are parallel to the first strip-shaped saw teeth. In the present invention, the height of a single first strip-shaped saw tooth is preferably 8 to 10 mm, and the width is preferably 8 to 10 mm; the spacing between adjacent first strip-shaped saw teeth (i.e., the spacing between the blank areas between adjacent first strip-shaped saw teeth) is preferably 10 to 20 mm. In the present invention, the top surface (i.e., the surface facing the first silicone membrane) of a single second strip-shaped saw tooth is preferably 8 to 12 mm wide, the bottom surface is preferably 4 to 6 mm wide, the height is preferably 8 to 12 mm, and the spacing between adjacent second strip-shaped saw teeth (i.e., the spacing between the top surfaces of adjacent second strip-shaped saw teeth) is preferably 20 to 25 mm. The present invention limits the sizes of the first strip-shaped serrations and the second strip-shaped serrations, which can provide as many irreversible anchoring structures as possible on the basis of ensuring the penetration of the mortar into the decorative layer, thereby improving the bonding effect between the filling layer and the decorative layer. Figure 5 This is a schematic diagram of the sawtooth on the side of the second silicone film. Figure 6 Schematic diagram of the serrations on the bottom surface of the second silicone film.
[0057] The present invention sets the side wall of the second silicone film into a sawtooth with a square cross-section, which is beneficial to the rapid discharge of air bubbles to form a complete sawtooth structure when the decorative layer cement slurry is filled, and is beneficial to the full fit between the subsequent filler and the side wall of the decorative layer, forming an irreversible mechanical bite effect. The present invention sets the bottom surface of the second silicone film into a sawtooth with a chamfered pyramid structure, which can effectively discharge air under the action of the gravity and vibration of the cement slurry, eliminating the problem of the negative angle formed by the chamfered pyramid sawtooth and the plane affecting the slurry filling. More importantly, the chamfered pyramid sawtooth structure provides an irreversible mortise and tenon structure for the subsequent filler, greatly improving the adhesion between the decorative layer and the filler. The bonding problem between the new mortar and the old mortar interface has always been a difficult problem in the industry. The usual practice is to spray an interface agent on the surface of the old mortar or to create a rough surface by roughening. However, the cost and quality of the interface agent and the unevenness of the rough surface made by roughening still cannot completely solve this problem. The chamfered serrated structure provided in the present invention has a size that fully takes into account the penetration of the slurry, and is arranged in an orderly manner, with a sufficient number and a reasonable spacing. There is no need to consider the bonding effect formed by the hydration reaction at the interface between the new and old mortars. The serrated groove structure of its structure can provide sufficient mechanical bite force, because the negative angle structure of the chamfered serrated groove allows the inflowing slurry to form an irreversible mortise and tenon structure, and after hardening, the filling layer cannot produce an upward, downward, leftward or right displacement, thereby achieving a "bonding" effect, thereby solving a technical difficulty in the industry.
[0058] In the present invention, the connection between the second silicone film and each surface of the first silicone film is preferably a rounded corner (i.e., chamfered corner), such as Figure 3 In the present invention, each edge connection of the second silicone membrane is rounded, which can disperse the tensile stress of the subsequent mortar at the interface between the filling layer and the facing shell.
[0059] The present invention has no special requirements for the preparation methods of the first silicone film and the second silicone film. The corresponding silicone films meeting the above requirements can be obtained by using methods well known to those skilled in the art. For example, to prepare a silicone film with a smooth surface (such as a mirror effect), a smooth or polished silicone "master mold" can be used for reverse molding to replicate a large number of mirror silicones.
[0060] In the present invention, the assembly method of the mold for preparing the imitation stone tile decorative layer is preferably:
[0061] The outer mold and the inner mold are fixed by a fixing clamp (with fixing screws), and a distance is reserved between the outer mold and the inner mold;
[0062] The first silicone film and the second silicone film are respectively pressed against the inner wall of the outer mold and the outer wall of the inner mold, and the two silicone films are clamped on the upper edges of the outer mold and the inner mold.
[0063] In the present invention, the size of the first silicone membrane is equal to the inner diameter of the outer mold; the inner diameter of the second silicone membrane is preferably 10 to 15 mm smaller than the length, width and height of the outer diameter of the inner mold, so as to clamp the silicone membrane and improve the dimensional accuracy of the internal cavity.
[0064] The mold provided by the present invention can realize the preparation of imitation stone tiles with various patterns under the same mold frame, while omitting the process of cutting, grinding, polishing and the like, thus saving the preparation cost.
[0065] The present invention provides a method for preparing a stone-like surface tile, comprising the following steps:
[0066] Pour the color paste into the main paste, inject the obtained paste into the space between the first silicone film and the second silicone film in the mold described in the above technical solution for molding, and obtain the stone decorative shell blank after demoulding;
[0067] Curing the stone decorative shell blank to obtain a stone decorative shell;
[0068] The cavity of the stone decorative shell is filled with recycled concrete or recycled mortar to obtain the imitation stone facing brick.
[0069] In the present invention, unless otherwise specified, the raw materials involved are commercially available products well known in the art.
[0070] The present invention pours the color paste into the main paste, injects the obtained paste into the space between the first silicone film and the second silicone film in the mold described in the above technical solution for molding, and obtains the stone decoration shell blank after demoulding.
[0071] In the present invention, the main slurry includes the following components in parts by mass: 220-300 parts of white cement, 15-30 parts of silica fume, 60-130 parts of mineral powder, 1-5 parts of redispersible latex powder, 1-5 parts of attapulgite, 180-250 parts of heavy calcium carbonate, 1-3 parts of short fibers, 30-90 parts of first regenerated sand, 60-150 parts of second regenerated sand, 90-180 parts of third regenerated sand, 200-300 parts of fourth regenerated sand, 120-200 parts of regenerated stone powder, 1-5 parts of defoaming agent, 3-8 parts of styrene-acrylic emulsion, 10-15 parts of water reducer, and 180-210 parts of water. In the present invention, in terms of parts by mass, the white cement in the main slurry may be 225, 250, 270 or 300 parts, the silica fume may be 15, 20, 25 or 30 parts, the mineral powder may be 60, 80, 100 or 130 parts, the redispersible latex powder may be 1, 3 or 5 parts, the attapulgite may be 1, 2, 3, 4 or 5 parts, the heavy calcium carbonate may be 180, 200 or 250 parts, the short fiber may be 1, 2 or 3 parts, the first regenerated sand may be 30, 50, 60, 80, 100 or 130 parts, the redispersible latex powder may be 1, 3 or 5 parts, the attapulgite may be 1, 2, 3, 4 or 5 parts, the heavy calcium carbonate may be 180, 200 or 250 parts, the short fiber may be 1, 2 or 3 parts, and the first regenerated sand may be 30, 50, 60, 80, 100 or 130 parts. The amount of the regenerated sand can be 70, 100, 130 or 150 parts, the amount of the second regenerated sand can be 60, 100, 130 or 150 parts, the amount of the third regenerated sand can be 90, 100, 130, 150 or 180 parts, the amount of the fourth regenerated sand can be 200, 250 or 300 parts, the amount of the regenerated stone powder can be 120, 130, 150 or 200 parts, the amount of the defoaming agent can be 1, 3 or 5 parts, the amount of the styrene-acrylic emulsion can be 3, 5 or 8 parts, the amount of the water reducer can be 10, 12 or 15 parts, and the amount of water can be 180, 200 or 210 parts.
[0072] In the present invention, the white cement is preferably ordinary Portland cement, and the strength grade of the ordinary Portland cement is preferably P.O42.5 or above. In the present invention, the silica fume is preferably the silica fume specified in GB / T 18736 "Mineral admixtures for high-strength and high-performance concrete", and the specific surface area of the silica fume is preferably 20 to 28 m 2 / g, and the average particle size is preferably 0.1-0.3μm. In the present invention, the mineral powder is preferably S95 grade mineral powder specified in GB / T18046 "Granulated blast furnace slag powder for cement and concrete". The present invention has no special requirements for the dispersible latex powder, attapulgite and heavy calcium carbonate, and conventional commercial products in the field can be used. In the present invention, the short fiber is preferably polypropylene fiber, and the length is preferably 8-10mm.
[0073] In the present invention, the particle size of the first regenerated sand is 1.25-2.5 mm, the particle size of the second regenerated sand is 0.63-1.25 mm, the particle size of the third regenerated sand is 0.315-0.63 mm, and the particle size of the fourth regenerated sand is 0.15-0.315 mm. The first regenerated sand, the second regenerated sand, the third regenerated sand, and the fourth regenerated sand are preferably regenerated sands obtained by screening after crushing waste concrete, and waste steel slag and / or slag may also be mixed into the waste concrete. When the total mass of the first regenerated sand, the second regenerated sand, the third regenerated sand, and the fourth regenerated sand is 100%, the mass proportions of the first regenerated sand, the second regenerated sand, the third regenerated sand, and the fourth regenerated sand are preferably 5-15%, 10-25%, 25-35%, and 30-37%, respectively. In the present invention, the regenerated stone powder is preferably the regenerated stone powder ball-milled after crushing of waste concrete or waste aerated concrete, and the waste concrete or waste aerated concrete may also be mixed with waste steel slag and / or slag; the particle size of the regenerated stone powder is preferably less than 0.045 mm. Regenerated sand and regenerated stone powder, these raw materials are crushed and screened from waste buildings (including natural sand and stone minerals), waste steel slag, and slag, and their particles contain different degrees of iron and nickel components; different proportions can be set according to the different requirements of the tiles for wear resistance. When there is a wear resistance requirement, the weight proportion of waste steel slag and slag in the regenerated sand and regenerated stone powder is preferably more than 50%, and when there is no wear resistance requirement, the weight proportion of waste steel slag and slag is preferably less than 25%.
[0074] In the present invention, the defoamer is preferably a polyether defoamer, and the water reducer is preferably a polycarboxylic acid water reducer. The present invention has no special requirements for the polyether defoamer, polycarboxylic acid water reducer and styrene acrylic emulsion, and the corresponding admixtures well known to those skilled in the art can be used. In the present invention, the water is preferably water in accordance with JGJ 63 "Standard for Water for Concrete Mixing".
[0075] In the present invention, the white cement, silica fume, and mineral powder are hydraulic binders for the decorative layer slurry, the redispersible latex powder and attapulgite are functional additives for the slurry to play the role of suspension and thickening, the short fibers and various types of regenerated sand are the skeleton of the slurry, the heavy calcium carbonate and regenerated stone powder are the fillers in the gaps between the skeletons, the defoamer, styrene acrylic emulsion, and water reducer are liquid functional additives to play the role of reducing water, defoaming, and increasing the flow properties of the slurry fluid. In the present invention, the main slurry is a high-flowability self-compacting slurry, which is combined with a mirror-finished silicone film layer, and the cutting and polishing processes can be directly omitted.
[0076] In the present invention, the main slurry preferably further comprises 1 to 3 parts of a wetting agent. In the present invention, the wetting agent is preferably a non-ionic wetting agent, and the non-ionic wetting agent is preferably PE-100 wetting agent produced by Guangzhou Kuangxuan Chemical Co., Ltd.
[0077] In the present invention, the mixing steps of the main slurry are preferably: white cement, silica fume, mineral powder, redispersible latex powder, attapulgite, heavy calcium carbonate, short fiber, first regenerated sand, second regenerated sand, third regenerated sand, fourth regenerated sand and regenerated stone powder are put into a planetary mixer for first mixing to obtain a first mixture; styrene acrylic emulsion and part of water are mixed and poured into the first mixture for second mixing; after the dry material is moistened, a water reducer is added for third mixing; after pulping, a defoamer is added for fourth mixing, and finally the remaining water is added thereto and stirred evenly, and the mixture is removed from the pot after standing to obtain the main slurry. In the present invention, the rotation speed of the planetary mixer is preferably 60r / min, the time of the first stirring is preferably 1min, and the part of water is preferably 80% of the total water mass used to prepare the main slurry; the time of the second stirring is preferably 1min; the time of the third stirring is based on the mixing of the water reducer; the time of the fourth stirring is preferably 1min; and the time of standing is preferably 5min. In the present invention, when the main paste also includes a wetting agent, the present invention preferably adds the wetting agent to the main paste before it is taken out of the pot, and stirs (the stirring blade is close to the liquid surface or penetrates 0.5 to 1 cm into the liquid surface for shallow stirring) for 5 to 10 seconds. The present invention adds a wetting agent to the surface of the main paste, which can reduce the surface tension of the contact interface between the color paste and the main paste, so that the color paste is slightly mixed at the interface, that is, it presents a color halo similar to a landscape painting, so as to form a more realistic imitation stone texture effect.
[0078] In the present invention, the color paste includes the following components by mass: 220-300 parts of white cement, 15-30 parts of silica fume, 60-130 parts of mineral powder, 1-5 parts of redispersible latex powder, 1-5 parts of attapulgite, 180-250 parts of heavy calcium carbonate, 1-3 parts of short fibers, 30-90 parts of first regenerated sand, 60-150 parts of second regenerated sand, 90-180 parts of third regenerated sand, 200-300 parts of fourth regenerated sand, 120-200 parts of regenerated stone powder, 1-5 parts of defoamer, 3-8 parts of styrene-acrylic emulsion, 10-15 parts of water reducer, 20-35 parts of pigment, and 180-210 parts of water. Except for the pigment, each component in the color paste is preferably the same as the corresponding component in the main paste, and will not be repeated here. In the present invention, the pigment plays the role of manufacturing imitation stone patterns. In an embodiment of the present invention, the pigment is an inorganic iron oxide pigment. In the present invention, the mixing steps of the color paste are the same as those of the main paste, and the pigment is only added in the first stirring step.
[0079] In the present invention, the main paste is the main color of the imitation stone decorative shell, and the color paste is the color of the imitation stone texture. The present invention can adjust the color of the color paste by the type of pigment, so as to obtain color pastes of different colors respectively. The present invention can pour one color paste into the main paste, or pour multiple color pastes, and operate according to the color requirements of the imitation stone tile decorative layer. The mass ratio of each color paste to the main paste is preferably 25:1. The present invention preferably pours the color paste slowly into the main paste, and the color paste will flow into the mold with the main paste, and naturally spread in the silicone membrane with the main paste and cover the bottom of the mold. This process does not require stirring and vibration; wherein, the color paste and the main paste will not interpenetrate each other, because: pigments are added to the color paste, so there is a difference in density with the main paste, and the viscosity of the color paste and the main paste is different under the same water consumption, and their surface tension is different under the premise of no stirring; in addition, attapulgite gives the slurry thixotropic properties, and the two slurries are in a relatively stable suspension state without stirring and are not easy to interpenetrate each other.
[0080] After the slurry is injected, the present invention preferably moves the mold filled with the slurry into an electromagnetic vibration table for vibration, the frequency is set to 50Hz, the vibration direction is vertical, the vibration time is 3s, the amplitude is set to 2mm, and then the vibration direction is adjusted to continue to vibrate for 3s, and then the imitation stone color and texture are formed. In the present invention, the color paste automatically spreads with the flow of the main paste to form a random texture prototype; the divergent color halo at the interface of the color paste and the main paste diffuses under the condition of vibration to further form a texture.
[0081] In the present invention, preferably, compressed gas is charged into the inflation hole reserved in the center of the bottom plate of the outer mold by a compressor to realize demoulding of the outer mold. The present invention has no special requirements for the demoulding method of the inner mold, and the demoulding can be realized by a demoulding method well known to those skilled in the art, such as removing the split inner molds separately and then tearing off the second silicone film.
[0082] After obtaining the stone decoration shell blank, the present invention performs curing on the stone decoration shell blank to obtain the stone decoration shell.
[0083] In the present invention, the curing is preferably to water and seal the stone decorative shell blank, and the curing time is preferably 3 days.
[0084] After obtaining the stone decorative shell, the present invention fills the cavity of the stone decorative shell (the space formed after the outer mold is demoulded) with recycled concrete or recycled mortar to obtain the imitation stone facing brick.
[0085] In the present invention, the recycled concrete or recycled mortar is preferably prepared from construction waste. In the present invention, the recycled mortar or recycled concrete is filled according to the different strength grades of the imitation stone tiles, specifically, the strength grade requirements of the standard GB / T28635-2012 "Concrete Pavement Bricks" are matched with the corresponding strength grade of the recycled concrete or recycled mortar. For example, when the compressive strength grade of the imitation stone tiles is C C When the strength grade of the imitation stone facing brick is C40, the thickness of the imitation stone facing layer is set to 12mm~15mm, and the recycled concrete or recycled mortar with the strength grade of C40 is filled in. C When the imitation stone facing brick is of strength grade C50, the thickness of the imitation stone facing layer is set to 15mm-18mm, and the recycled concrete or recycled mortar with strength grade C50 is filled in; when the strength grade of the imitation stone facing brick is C C When the thickness of the imitation stone facing layer is 20 mm to 25 mm, the recycled concrete or recycled mortar with a strength grade of C60 is filled in. In the present invention, the recycled concrete or recycled mortar may also be embedded with waste concrete blocks and bricks of the same strength. After the recycled concrete or recycled mortar is filled in, the film is sealed and covered for maintenance.
[0086] Since the early drying shrinkage of the decorative shell occurs as a whole without external interference, the only factor causing the shrinkage and cracking of the material is the raw material system itself. The present invention successfully suppresses the early shrinkage and cracking of the decorative layer shell in the early stage of strength development by adding short fibers, polymer powder, emulsion and aggregate particle size according to the standard grading curve and adding mineral admixtures to the cementitious material system to reduce the shrinkage rate of the cement hydration reaction until the shell strength can completely overcome its own shrinkage stress. After the maintenance is completed, the cavity is filled with newly mixed recycled mortar or recycled concrete. At this time, the serrated structure on the inner surface of the decorative layer shell can provide a strong mechanical bite force, which can effectively compensate for or even provide a sufficient fitting effect without relying on the bonding of the new and old mortar interfaces.
[0087] With the continuous advancement of urbanization, the demolition of old buildings and the construction of new buildings have brought about a huge amount of construction waste. The past fixed-site disposal and simple landfill treatment methods can no longer meet the needs of urban development. How to resource-process construction waste has become a practical problem that needs to be solved urgently. The present invention has developed a new preparation process for imitation stone facing tiles, which can consume a large amount of construction waste while taking into account the technical advantages of the mainstream imitation stone brick production process on the market, and prepare various types of imitation stone bricks at low cost, providing new ideas for the development of the industry. The preparation method provided by the present invention can directly prepare a smooth decorative layer without additional processes, and at the same time solves the problem of easy cracking of the cement-based facing layer.
[0088] The present invention provides a stone-like facing brick prepared by the preparation method described in the above technical solution, wherein the stone-like facing brick comprises a stone decoration shell and a filling layer combined in the cavity of the stone decoration shell, wherein the filling layer is recycled concrete or recycled mortar, and the interface between the stone decoration shell and the filling layer forms a mechanical bite through a sawtooth structure. The structure of the stone-like facing brick provided by the present invention is as follows Figure 7 shown.
[0089] To further illustrate the present invention, the mold for preparing the imitation stone facing tile decorative layer and the imitation stone facing tile and the preparation method thereof provided by the present invention are described in detail below in conjunction with examples, but they should not be construed as limiting the scope of protection of the present invention.
[0090] In Examples 1 to 3, Figure 1 to Figure 3 The mold shown (the second silicone film side and bottom serrations are as shown Figure 5-6 As shown in the figure), the imitation stone facing brick decorative layer is prepared. Figure 1 1-outer mold, 2-inner mold, 3-first silicone membrane, 4-second silicone membrane, 5-inner and outer mold fixing clamps, 6-fixing screws, 7-inflating hole; wherein the Shore hardness of the first silicone membrane is 28HA, and the Shore hardness of the second silicone membrane is 35HA; the side of the second silicone membrane is provided with strip serrations with square cross-sections (arranged horizontally and in parallel), and the bottom is provided with chamfered pyramid-shaped strip serrations (parallel to the side serrations), the height of a single square strip serration is 8mm, the width is 8mm, and the spacing between adjacent serrations is 15mm; the top surface width of a single chamfered pyramid-shaped serration (i.e. the side facing the first silicone membrane) is 8mm, the bottom surface width is 4mm, the height is 8mm, and the spacing between adjacent serrations is 20mm; the connection between the second silicone membrane and each surface of the first silicone membrane is rounded.
[0091] The “parts” in Examples 1 to 3 are all “parts by mass”; the specific surface area of silica fume is 20 to 28 m 2 / g, with an average particle size of 0.1-0.3 μm; the redispersible latex powder was purchased from Shanxi Sanwei Group Co., Ltd., model SWF-05; the styrene acrylic emulsion was purchased from Zhengzhou Kailing New Materials Co., Ltd., with a solid content of ≥48wt% and a viscosity of 3000mPa.s.
[0092] Example 1
[0093] The thickness of the decorative shell is set to 1 cm, and a mold combination with an internal space spacing of 1 cm is selected. The outer dimensions of the decorative shell prepared by the mold are 300×300×60 mm. The decorative shell slurry is prepared as follows:
[0094] Main slurry: 250 parts of 52.5 grade white cement, 20 parts of silica fume, 80 parts of S95 grade mineral powder, 3 parts of redispersible latex powder, 3 parts of attapulgite, 200 parts of heavy calcium carbonate, 3 parts of polypropylene short fiber (length 8-10mm), 70 parts of regenerated sand (particle size 1.25-2.5mm), 130 parts of regenerated sand (particle size 0.63-1.25mm), 138 parts of regenerated sand (particle size 0.315-0.63mm), 200 parts of regenerated sand (0.15-0.315mm), 130 parts of regenerated stone powder (particle size below 0.045mm), 3 parts of polyether defoamer, 5 parts of styrene-acrylic emulsion, 12 parts of polycarboxylic acid water reducer, and 200 parts of water;
[0095] Color paste: 250 parts of 52.5 grade white cement, 20 parts of silica fume, 80 parts of S95 grade mineral powder, 3 parts of redispersible latex powder, 3 parts of attapulgite, 200 parts of heavy calcium carbonate, 3 parts of polypropylene staple fiber (length 8-10mm), 70 parts of regenerated sand (particle size 1.25-2.5mm), 130 parts of regenerated sand (particle size 0.63-1.25mm), 138 parts of regenerated sand (particle size 0.315-0.63mm), 200 parts of regenerated sand (0.15-0.315mm), 130 parts of regenerated stone powder (particle size below 0.045mm), 3 parts of polyether defoamer, 5 parts of styrene-acrylic emulsion, 12 parts of polycarboxylic acid water reducer, 30 parts of pigment (inorganic iron oxide pigment), and 200 parts of water; the regenerated sand in the main paste and color paste is obtained by screening after crushing waste concrete, and the regenerated stone powder is obtained by ball milling after crushing waste concrete.
[0096] The main slurry mixing steps are: put white cement, silica fume, mineral powder, redispersible latex powder, attapulgite, heavy calcium carbonate, polypropylene short fiber, regenerated sand (particle size 1.25-2.5mm), regenerated sand (particle size 0.63-1.25mm), regenerated sand (particle size 0.315-0.63mm), regenerated sand (0.15-0.315mm), regenerated stone powder (particle size 0.045) into a planetary mixer, set the speed to 60r / min, and dry stir for 1min; then mix the styrene acrylic emulsion and 80% of the water and pour it into the stirring pot and continue to stir for 1min, add polycarboxylic acid water reducer after the dry material is moistened and continue to stir, add polyether defoamer after slurrying and continue to stir for 1min, and finally add the remaining 20% of water into the pot and stir evenly, and it can be taken out of the pot after standing for 5min. The color paste mixing steps are the same as the main slurry, and the pigment can be added during the first step of dry stirring.
[0097] Preparation of decorative shell: Take one part of main paste and one part of color paste, with a mass ratio of 25:1. Slowly pour the color paste into the main paste and follow the main paste to flow in. Figure 1 to Figure 3The mold shown (the first silicone film is a smooth silicone film) does not need to be vibrated at this time. The color paste spreads naturally with the main paste in the silicone film and covers the bottom of the mold. It is then moved into an electromagnetic vibration table for vibration. The frequency is set to 50 Hz, the vibration direction is vertical, the vibration time is 3s, the amplitude is set to 2mm, and then the vibration direction is adjusted to continue vibrating for 3s. After the decorative shell material hardens and is demolded, it is watered and sealed for maintenance for 3 days to obtain a decorative shell.
[0098] Preparation of imitation stone tiles: Fill the cavity of the decorative shell after the above curing with C50 recycled concrete, then embed discarded concrete blocks and bricks of equal strength, seal and cover with a film for curing, and prepare imitation stone tiles.
[0099] The prepared imitation stone tiles were tested. The testing method is as follows: the size deviation is in accordance with the requirements of Table 2 and Table 3 of the standard JC / T2604-2021 "Imitation Stone Concrete Panels and Tiles"; the top surface's missing edges, missing corners and color spots in the appearance quality are in accordance with the requirements for superior products in Table 8 of GB / T 18601-2009, and the cracks, missing edges, corners, sticking and defects on other surfaces are in accordance with the requirements of Table 3 of GB / T 25993-2010; the compressive strength is in accordance with the requirements of Table 5 and Appendix C of the standard JC / T 2604-2021 "Imitation Stone Concrete Panels and Tiles"; the wear resistance is in accordance with the provisions of GB / T 12988. The test results are as follows:
[0100] Appearance quality: The number of cracks with a length of 3 to 10 mm shall meet the requirement of ≤2, and the number of cracks with a length of ≥10 mm or a gap width of >0.2 mm shall meet the requirement of 0;
[0101] Dimensional deviation: length difference meets the requirement of 1 / -2mm, width difference meets the requirement of 1 / -2mm, thickness difference meets the requirement of ±2mm, and diagonal difference meets the requirement of ≤5.0mm;
[0102] The 28-day compressive strength value is 52.5MPa;
[0103] The wear resistance value is 2.1.
[0104] The test blocks of the decorative shell material were retained and the average compressive strength / flexural strength test was carried out according to the standard GB / T17671 "Test Method for Cement Mortar Strength", and the test block size was 160×40×40mm. Test results: 28-day average compressive strength of 55MPa, 28-day average flexural strength of 6.50MPa.
[0105] Figure 8 This is an appearance effect diagram of the decorative layer of the imitation stone facing brick prepared in Example 1. Fig. 9 This is a wrapping effect diagram of the decorative shell + filling layer of the imitation stone facing brick prepared in Example 1.
[0106] Example 2
[0107] The thickness of the decorative shell is set to 1.5 cm, and a mold combination with an internal space spacing of 1.5 cm is selected. The outer dimensions of the decorative shell prepared by the mold are 300×300×60 mm, and the slurry ratio of the decorative shell is:
[0108] Main slurry: 300 parts of 52.5 grade white cement, 30 parts of silica fume, 120 parts of S95 grade mineral powder, 3 parts of redispersible latex powder, 3 parts of attapulgite, 200 parts of heavy calcium carbonate, 3 parts of polypropylene short fiber (length 8-10mm), 70 parts of regenerated sand (particle size 1.25-2.5mm), 130 parts of regenerated sand (particle size 0.63-1.25mm), 138 parts of regenerated sand (particle size 0.315-0.63mm), 200 parts of regenerated sand (0.15-0.315mm), 130 parts of regenerated stone powder (particle size below 0.045mm), 3 parts of polyether defoamer, 5 parts of styrene-acrylic emulsion, 12 parts of polycarboxylic acid water reducer, and 200 parts of water;
[0109] Color paste: 300 parts of 52.5 grade white cement, 30 parts of silica fume, 120 parts of S95 grade mineral powder, 3 parts of redispersible latex powder, 3 parts of attapulgite, 200 parts of heavy calcium carbonate, 3 parts of polypropylene short fiber (length 8-10mm), 70 parts of regenerated sand (particle size 1.25-2.5mm), 130 parts of regenerated sand (particle size 0.63-1.25mm), 130 parts of regenerated sand (particle size 0.315-0.63 The main slurry and color paste are prepared by mixing 138 parts of recycled sand (0.15-0.315 mm), 200 parts of recycled sand, 130 parts of recycled stone powder (particle size below 0.045 mm), 3 parts of polyether defoamer, 5 parts of styrene-acrylic emulsion, 12 parts of polycarboxylic acid water reducer, 30 parts of pigment (inorganic iron oxide pigment), and 200 parts of water; the recycled sand in the main slurry and color paste is obtained by sieving after crushing waste concrete, and the recycled stone powder is obtained by ball milling after crushing waste concrete.
[0110] The steps of mixing the main paste and the color paste are the same as those in Example 1.
[0111] Preparation of decorative shell: Take one part of main paste and one part of color paste, with a mass ratio of 25:1. Slowly pour the color paste into the main paste and follow the main paste to flow in. Figure 1 to Figure 3 The mold shown (the first silicone film is a smooth silicone film) does not need to be vibrated at this time. The color paste spreads naturally with the main paste in the silicone film and covers the bottom of the mold. It is then moved into an electromagnetic vibration table for vibration. The frequency is set to 50 Hz, the vibration direction is vertical, the vibration time is 3s, and the amplitude is set to 2mm. The vibration direction is then adjusted and vibration continues for 3s. After the decorative shell material hardens and is demolded, it is watered and sealed for 3 days to obtain a decorative shell.
[0112] Preparation of imitation stone tiles: After the above-mentioned curing is completed, the cavity is filled with C60 recycled concrete or poured with recycled mortar of equal strength, and then discarded concrete blocks and bricks of equal strength are embedded to prepare imitation stone tiles.
[0113] The prepared imitation stone tiles were tested using the same testing method as in Example 1. The test results are as follows:
[0114] Appearance quality: The number of cracks with a length of 3 to 10 mm shall meet the requirement of ≤2, and the number of cracks with a length of ≥10 mm or a gap width of >0.2 mm shall meet the requirement of 0;
[0115] Dimensional deviation: length difference meets the requirement of 1 / -2mm, width difference meets the requirement of 1 / -2mm, thickness difference meets the requirement of ±2mm, and diagonal difference meets the requirement of ≤5.0mm;
[0116] The 28-day compressive strength value is 63.8MPa;
[0117] The wear resistance value is 2.3.
[0118] The test blocks of the decorative shell material were retained and the average compressive strength / flexural strength test was carried out according to the standard GB / T17671 "Test Method for Cement Mortar Strength", and the test block size was 160×40×40mm. Test results: 28-day average compressive strength was 65MPa, and 28-day average flexural strength was 8.30MPa.
[0119] Example 3
[0120] The thickness of the decorative shell is set to 1.0 cm, and a mold combination with an internal space spacing of 1.0 cm is selected. The outer dimensions of the decorative shell prepared by the mold are 300×300×60 mm. Due to the increased demand for wear resistance, steel slag and slag containing iron and nickel components are added to the regenerated sand and regenerated stone powder.
[0121] The slurry ratio of the decorative shell is as follows: main slurry: 250 parts of 52.5 grade white cement, 20 parts of silica fume, 80 parts of S95 grade mineral powder, 3 parts of redispersible latex powder, 3 parts of attapulgite, 200 parts of heavy calcium carbonate, 3 parts of polypropylene short fiber (length 8-10mm), 70 parts of regenerated sand (particle size 1.25-2.5mm), 130 parts of regenerated sand (particle size 0.63-1.25mm), 100 parts of regenerated sand (particle size 1.25-2.5mm), 100 parts of regenerated sand (particle size 0.63-1.2 ... 138 parts of recycled sand (0.15-0.315mm), 200 parts of recycled stone powder (particle size 0.045mm or less), 3 parts of polyether defoamer, 5 parts of styrene-acrylic emulsion, 12 parts of polycarboxylic acid water reducer, 200 parts of water; color paste: 250 parts of 52.5 grade white cement, 20 parts of silica fume, 80 parts of S95 grade mineral powder, 3 parts of redispersible latex powder, 3 parts of attapulgite, 200 parts of heavy calcium carbonate, 3 parts of polypropylene staple fibers (length 8-10 mm), 70 parts of regenerated sand (particle size 1.25-2.5 mm), 130 parts of regenerated sand (particle size 0.63-1.25 mm), 138 parts of regenerated sand (particle size 0.315-0.63 mm), 200 parts of regenerated sand (0.15-0.315 mm), 130 parts of regenerated stone powder (particle size below 0.045 mm), 3 parts of polyether defoamer, 5 parts of styrene-acrylic emulsion, 12 parts of polycarboxylic acid water reducer, 30 parts of pigment (inorganic iron oxide pigment), and 200 parts of water; the regenerated sand in the main slurry and the color paste is obtained by crushing and sieving waste concrete, steel slag and slag (the mass ratio of steel slag to slag is 50%), and the regenerated stone powder is obtained by crushing and ball milling waste concrete, steel slag and slag (the mass ratio of steel slag to slag is 50%).
[0122] The steps of mixing the main paste and the color paste are the same as those in Example 1.
[0123] Preparation of decorative shell: Take one part of main paste and one part of color paste, with a mass ratio of 25:1. Slowly pour the color paste into the main paste and follow the main paste to flow in. Figure 1 to Figure 3 The mold shown (the first silicone film is a smooth silicone film) does not need to be vibrated at this time. The color paste is naturally spread out in the silicone film with the main paste and covers the bottom of the mold. Then it is moved into the electromagnetic vibration table for vibration. The frequency is set to 50Hz, the vibration direction is vertical, the vibration time is 3s, the amplitude is set to 2mm, and then the vibration direction is adjusted to continue vibrating for 3s; after the decorative shell material is hardened and demolded, it is watered and sealed for 3 days to obtain a decorative shell. The first silicone film is a magnetic silicone film, and the preparation method is as follows:
[0124] Raw materials: 900 parts of liquid silicone, 550 parts of pure iron particles, 6.5 parts of silane coupling agent, and 30 parts of curing agent; among them, the liquid silicone has a Shore hardness of 25-28HA and a dynamic viscosity of 25,000±0.2 thousand Pa·s, specifically the cultural stone mold silicone produced by Shenzhen Hongtu Silicone Technology Co., Ltd., and the curing agent is the vulcanizing agent supporting Shenzhen Hongtu Silicone Technology Co., Ltd.; the particle size of the pure iron particles is 0.15-0.315mm, purchased from Shenzhen Chuanghui Metal Materials Factory;
[0125] The above raw materials were poured into a planetary mixer according to the specified mass fraction, the speed was set to 100 r / min, the stirring time was 2 to 3 min, and then cast on the surface of the mold (i.e., the silicone master mold, such as Figure 4 As shown) and sent to an oven at a temperature of 80°C. After curing for 4 hours, the mold was removed to obtain a semi-finished silica gel product;
[0126] The silica gel semi-finished product containing pure iron particles is stretched out and put into a brick mold. The inside of the brick mold is covered with magnet blocks with strong magnetism. The magnets magnetize the iron powder evenly dispersed in the silica gel semi-finished product. The magnetization time is 24 hours to obtain a magnetic silica gel film, namely the first silica gel film; the magnet block is a permanent ferrite magnet with an outer size of 20×10×5mm and a magnet brand of Y32, which is produced by Dongguan Saishi Magnetic and Electric Technology Co., Ltd.
[0127] Preparation of imitation stone tiles: fill the cavity of the decorative shell after the above curing with C50 recycled concrete or pour recycled mortar of equal strength, then embed discarded concrete blocks and bricks of equal strength, seal and cover with a film for curing, and prepare imitation stone tiles.
[0128] The prepared imitation stone tiles were tested using the same testing method as in Example 1. The test results are as follows:
[0129] Appearance quality: The number of cracks with a length of 3 to 10 mm shall meet the requirement of ≤2, and the number of cracks with a length of ≥10 mm or a gap width of >0.2 mm shall meet the requirement of 0;
[0130] Dimensional deviation: length difference meets the requirement of 1 / -2mm, width difference meets the requirement of 1 / -2mm, thickness difference meets the requirement of ±2mm, and diagonal difference meets the requirement of ≤5.0mm;
[0131] The 28-day compressive strength value is 54.8MPa;
[0132] The wear resistance value is 2.9.
[0133] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.
Claims
1. A mold for preparing a decorative layer of imitation stone tiles, characterized in that: It includes an outer mold, an inner mold, a first silicone film attached to the inner wall surface of the outer mold, and a second silicone film attached to the outer wall surface of the inner mold; The outer mold and the inner mold both have groove structures, and the first silicone film and the second silicone film are opposite to each other and a space is formed between them; The first silicone film is a smooth silicone film or a silicone film with imitation stone patterns engraved on the surface; the second silicone film is provided with a plurality of first strip saw teeth arranged horizontally and in parallel on the side relative to the first silicone film, and a plurality of second strip saw teeth arranged in parallel on the bottom surface, the cross-section of the first strip saw teeth is square, the second strip saw teeth are inverted pyramidal shapes, and the second strip saw teeth are parallel to the first strip saw teeth.
2. The mold for preparing a stone-like surface tile decorative layer according to claim 1, characterized in that: The thickness of the first silicone film is 3-5 mm, and the Shore hardness is 25-28 HA; the thickness of the second silicone film is 15-20 mm, and the Shore hardness is 28-35 HA.
3. The mold for preparing a stone-like surface tile decorative layer according to claim 1 or 2, characterized in that: The outer mold and the inner mold are made of steel; the first silicone film is magnetic.
4. The mold for preparing a stone-like surface tile decorative layer according to claim 1, characterized in that: The height of a single first strip-shaped sawtooth is 8 to 10 mm, and the width is 8 to 10 mm; the spacing between adjacent first strip-shaped sawtooths is 10 to 20 mm.
5. The mold for preparing a stone-like surface tile decorative layer according to claim 1, characterized in that: The top surface width of a single second strip-shaped sawtooth is 8 to 12 mm, the bottom surface width is 4 to 6 mm, the height is 8 to 12 mm, and the spacing between adjacent second strip-shaped sawtooths is 20 to 25 mm.
6. The mold for preparing a stone-like surface tile decorative layer according to claim 1, characterized in that: The connection between the second silicone film and each surface of the first silicone film is rounded.
7. A method for preparing a stone-like surface tile, characterized in that: The following steps are involved: Pour the color paste into the main paste, inject the obtained paste into the space between the first silicone film and the second silicone film in the mold according to any one of claims 1 to 6 for molding, and obtain the stone decorative shell blank after demolding; Curing the stone decorative shell blank to obtain a stone decorative shell; Filling the cavity of the stone decorative shell with recycled concrete or recycled mortar to obtain the imitation stone facing brick; The main slurry includes the following components in parts by weight: 220-300 parts of white cement, 15-30 parts of silica fume, 60-130 parts of mineral powder, 1-5 parts of redispersible latex powder, 1-5 parts of attapulgite, 180-250 parts of heavy calcium carbonate, 1-3 parts of short fiber, 30-90 parts of first regenerated sand, 60-150 parts of second regenerated sand, 90-180 parts of third regenerated sand, 200-300 parts of fourth regenerated sand, 120-200 parts of regenerated stone powder, 1-5 parts of defoamer, 3-8 parts of styrene-acrylic emulsion, 10-15 parts of water reducer, 180-210 parts of water; The color paste includes the following components in parts by weight: 220-300 parts of white cement, 15-30 parts of silica fume, 60-130 parts of mineral powder, 1-5 parts of redispersible latex powder, 1-5 parts of attapulgite, 180-250 parts of heavy calcium carbonate, 1-3 parts of short fiber, 30-90 parts of first regenerated sand, 60-150 parts of second regenerated sand, 90-180 parts of third regenerated sand, 200-300 parts of fourth regenerated sand, 120-200 parts of regenerated stone powder, 1-5 parts of defoamer, 3-8 parts of styrene-acrylic emulsion, 10-15 parts of water reducer, 20-35 parts of pigment, 180-210 parts of water; The particle size of the first regenerated sand is 1.25-2.5 mm, the particle size of the second regenerated sand is 0.63-1.25 mm, the particle size of the third regenerated sand is 0.315-0.63 mm, and the particle size of the fourth regenerated sand is 0.15-0.315 mm.
8. The preparation method according to claim 7, characterized in that: In the main paste and color paste, the white cement is ordinary Portland cement, and the strength grade of ordinary Portland cement is above P.O42.5; the specific surface area of silica fume is 20-28m 2 / g, with an average particle size of 0.1-0.3μm; the mineral powder is S95 grade mineral powder; the short fiber is polypropylene fiber with a length of 8-10mm; the particle size of the regenerated stone powder is below 0.045mm.
9. The preparation method according to claim 7, characterized in that: The main slurry also includes 1 to 3 parts of a wetting agent.
10. The imitation stone facing brick prepared by the preparation method according to any one of claims 7 to 9, the imitation stone facing brick comprising a stone decorative shell and a filling layer combined in the cavity of the stone decorative shell, the filling layer is recycled concrete or recycled mortar, and the interface between the stone decorative shell and the filling layer forms a mechanical bite through a serrated structure.
Citation Information
Cited By
A production forming mould for stone-like concrete precast blocks
CN224643920U